User Preferences of Airbnb Accommodation Spatially in The Special Region of Yogyakarta, Indonesia - Musthofa, Azis; Wicaksono, Arief; Rijanta, Raden (Jurnal Pembangunan Wilayah dan Kota, 2025)
The rise of sharing economy platforms has created a competition between hotels and Airbnb accommodations in filling the city space. Airbnb's accommodation concept is highly efficient in utilizing unused assets, aligning with SDG Goal 11. A large number of tourist visitors causes the development of Airbnb in The Special Region of Yogyakarta. An exploration of the preferences of Airbnb accommodation users will show the characteristics of tourists in terms of tourism demand. Airbnb data is sourced from Airdna, an analytics platform of Airbnb. Airbnb data consist of spatial and non-spatial data. For non-spatial Airbnb data, content analysis was used to explain the preferences of Airbnb accommodation users through reviews. Content analysis was carried out by categorized information units for each review and grouped it in form of positive (satisfied) or negative (dissatisfied). For Airbnb spatial data, spatial analysis was performed based on distribution patterns, proximity to road access and tourist sites, and the associations between accommodations and surrounding objects. Airbnb accommodations in Yogyakarta City and its surrounding areas are distributed across the region, with higher concentrations in tourist zones. Content analysis findings indicate that host hospitality receives the highest proportion of positive feedback from Airbnb users. Spatially, it shows that Airbnb accommodations in the Jetis and Kraton sub-districts achieve the most favorable ratings for amenities, location, hygiene, host and staff performance, as well as room and toilet conditions. In contrast, factors such as price, calmness, and building remain relatively uniform across all surveyed areas.